Strategic management approaches and applications in automotive retailing, with specific reference to the Western Cape - Kritzinger, Daniel Jacobus (Stellenbosch : Stellenbosch University, 2012)
Assignment (M.Comm.) -- University of Stellenbosch, 1999.